FORMATION OF ELITE RUSSIAN HIGHER EDUCATION AT THE BEGINNING OF THE XXITH CENTURY - Vitaliy G. Shishikin (Высшее образование в России)
The article focuses on the issues of formation of an elite segment of Russian higher school at the beginning of the XXIth century. After a lowBcontrolled process of a universitization of the 1990th the state used a new strategy in point of higher education institutions. Formation of a group of federal and national research universities has been carried out, combining administrative methods with competitive selection. As aresult, a number ofregional education institutions with high ranks in the system of higher education have raised their status. At the same time, the group of the elite included the littleBknown higher education institutions that have become new «growth points» branches within the country, but not on the international scene. The policy on forming of elite sector of higher school led to fixing of differentiation among higher education institutions, which took place before, but wasn’t legalized.